التخصص العلمي للمدرس و اثره على التحصيل الدراسي لتلاميذ السنة رابعة ابتدائي - معاش عمار; الأخضر بوزياني; الأمين عياط (My University, 2023)
The current study aimed to find out the relationship between the scientific specialization of the teacher and the academic achievement of the student in the primary stage in some of the elementary schools of the city of Laghouat, where the sample is the teacher. A form prepared by the researchers was used to collect information, and then the descriptive approach was used to suit the study, as well as the use of statistical methods, percentages and frequencies. The study concluded the following results: • A specialized teacher in the primary stage is very important, so we suggest setting up a specialized teacher for each subject, especially mathematics and the Arabic language, because the method of teaching varies from subject to subject. • Training courses for teachers before service are very important in order to know what should be provided to the student and set a period of not less than six months, because 51 days is not enough to know the needs of the student and get to know him, and because the student in the primary stage needs a teacher with professional experience. • Training seminars and forums for teachers are very important in order to look forward and get acquainted with all that is new in relation to the program and others. • Knowledge of the student's intellectual needs by the Ministry before setting up the program, by setting inquiries for teachers about what is going on in the department and what the student needs, and the program is not set randomly. • Knowing the teacher's attacks is very important because if we provide the teacher with what he needs in the department, we will have facilitated for him a threshold of teaching thresholds. • What are the basic needs of the student, especially intellectual ones, are very important, and this serves the development of the program. key words .The teacher - the learner - the primary stage - academic achievement